PENGARUH MEDIA KINCIR PERKALIAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS III SDN WONOKALANG SIDOARJO: Artikel Pendidikan - Diana Evawati; Triana Febrianti; Shofi Aulia Islami; Anggraeni Afria K (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Critical thinking is an essential 21st-century skill that needs to be instilled in students from elementary school. In reality, learning Mathematics especially multiplication remains a challenge for most students. They often struggle to grasp concepts and rarely have the opportunity to hone their critical thinking skills. This is because the learning process still relies heavily on traditional methods without the support of concrete media that can facilitate understanding. The presence of the multiplication wheel media is an innovation that can provide a more active, enjoyable, and meaningful learning experience. With this media, students are not only asked to memorize but also trained to recognize patterns, link concepts, and reason logically. This study highlights the effect of using the multiplication wheel media on the critical thinking skills of fourth-grade students at SDN Wonokalang Sidoarjo. The results obtained show a significant increase in the critical thinking skills of students who learn using this media compared to students who follow conventional learning. The application of the multiplication wheel media can foster curiosity, train problem-solving skills, and increase student active participation during the learning process. These findings confirm that the multiplication wheel is not only effective in strengthening understanding of multiplication concepts but also plays a crucial role in developing critical thinking skills. Therefore, elementary school mathematics teachers are encouraged to utilize concrete and innovative media such as the multiplication wheel to make learning more engaging and relevant to the demands of 21st-century skills.